Synaptotagmin 1 regulates cortical granule exocytosis during mouse oocyte activation. Issue 2 (2nd April 2020) - Zhu, Xiu-Lan; Li, Shi-Fen; Zhang, Xi-Qian; Xu, Hong; Luo, Yan-Qun; Yi, Yan-Hong; Lv, Li-Juan; Zhang, Chun-Hui; Wang, Zhen-Bo; Ouyang, Ying-Chun; Hou, Yi; Schatten, Heide; et al.
Summary: Synaptotagmin 1 (Syt1) is an abundant and important presynaptic vesicle protein that binds Ca 2+ for the regulation of synaptic vesicle exocytosis. Our previous study reported its localization and function on spindle assembly in mouse oocyte meiotic maturation. The present study was designed to investigate the function of Syt1 during mouse oocyte activation and subsequent cortical granule exocytosis (CGE) using confocal microscopy, morpholinol-based knockdown and time-lapse live cell imaging. By employing live cell imaging, we first studied the dynamic process of CGE and calculated the time interval between [Ca 2+ ]i rise and CGE after oocyte activation. We further showed that Syt1 was co-localized to cortical granules (CGs) at the oocyte cortex. After oocyte activation with SrCl2, the Syt1 distribution pattern was altered significantly, similar to the changes seen for the CGs. Knockdown of Syt1 inhibited [Ca 2+ ]i oscillations, disrupted the F-actin distribution pattern and delayed the time of cortical reaction. In summary, as a synaptic vesicle protein and calcium sensor for exocytosis, Syt1 acts as an essential regulator in mouse oocyte activation events including the generation of Ca 2+ signals and CGE.